The Influence of Work Environment, Workload, and Transformational Leadership on Employee Retention at Dira Café Kencong in Jember Regency - Camelia, Mirza Hidayatul; Satoto, Eko Budi; Izzuddin, Ahmad (Yayasan Sinergi Kawula Muda, 2025)
High employee turnover is a significant challenge for the service industry, including the culinary sector such as Dira Café Kencong in Jember Regency. A non-conducive work environment, unbalanced workload, and less than inspiring leadership are often the main factors in low employee retention. This research aims to analyze the influence of Work Environment, Workload, and Transformational Leadership on employee retention simultaneously or partially. The research method used is quantitative with a multiple linear regression approach. Data was collected from 75 employees through a questionnaire whose validity and reliability were tested. The research results show that the three independent variables have a significant influence on employee retention, with Transformational Leadership as the most dominant variable. Simultaneously, Work Environment, Workload, and Transformational Leadership explained 34.9% of the variation in employee retention. These results emphasize the importance of creating a supportive work environment, managing workload effectively, and strengthening a transformative leadership style to increase employee loyalty.